Differential Control of iNKT Cell Effector Lineage Differentiation by the Forkhead Box Protein O1 (Foxo1) Transcription Factor - Tao, Huishan; Li, Lei; Gao, Ying; Wang, Zehua; Zhong, Xiao-Ping (Frontiers in Immunology, 2019)
The invariant NKT (iNKT) cells recognize glycolipid antigens presented by the non-classical MHC like molecule CD1d. They represent an innate T-cell lineage with the ability to rapidly produce a variety of cytokines in response to agonist stimulation to bridge innate and adaptive immunity. In thymus, most iNKT cells complete their maturation and differentiate to multiple effector lineages such as iNKT-1, iNKT-2, and iNKT-17 cells that possess the capability to produce IFNg, IL-4, and IL-17A, respectively, and play distinct roles in immune responses and diseases. Mechanisms that control iNKT lineage fate decisions are still not well understood. Evidence has revealed critical roles of Foxo1 of the forkhead box O1 subfamily of transcription factors in the immune system. However, its role in iNKT cells has been unknown. In this report, we demonstrate that deletion of Foxo1 causes severe decreases of iNKT cell total numbers due to impairment of late but not early iNKT cell development. Deficiency of Foxo1 results in decreases of iNKT-1 but increases of iNKT-17 cells. Our data reveal that Foxo1 controls iNKT effector lineage fate decision by promoting iNKT-1 but suppressing iNKT-17 lineages.